Incorporation of MnO nanoparticles inside porous carbon nanotubes originated from conjugated microporous polymers for lithium storage. Issue 48 (25th November 2016) - Zhang, Qingtang; Dai, Qinqin; Li, Meng; Wang, Xiaomei; Li, An
Abstract : Porous carbon nanotubes were simply fabricated by the pyrolysis of conjugated microporous polymer nanotubes, followed by doping MnO nanoparticles inside of the nanotubes (MnO–PCNTs). MnO–PCNTs deliver superior electrochemical performance to PCNTs. Abstract : Porous carbon nanotubes (PCNTs) were synthesized and incorporation of MnO nanoparticles inside PCNTs (MnO–PCNTs) was successfully achieved by simple pyrolysis of conjugated microporous polymer (CMP) nanotubes and manganese acetate adsorbed CMP nanotubes, respectively. PCNTs exhibit good performance as anode materials for lithium ion batteries. The performance of PCNTs can be further enhanced by incorporation of MnO nanoparticles. MnO–PCNTs show excellent cycling stability (572.6 mA h g −1 after 300 cycles at 1C) and large rate performance (160.8 mA h g −1 at 30C), which are much higher than carbon nanotubes (CNTs) supported MnO composites (MnO–CNTs). This may be due to the unique structure of MnO–PCNTs, where MnO nanoparticles are located inside the tubes, preferably resolving the pulverization issue of MnO during repeated charge–discharge cycles.